2015
DOI: 10.1890/14-0743.1
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐stressor impacts on fungal diversity and ecosystem functions in streams: natural vs. anthropogenic stress

Abstract: Biological assemblages are often subjected to multiple stressors emerging from both anthropogenic activities and naturally stressful conditions, and species' responses to simultaneous stressors may differ from those predicted based on the individual effects of each stressor alone. We studied the influence of land-use disturbance (forest drainage) on fungal decomposer assemblages and leaf decomposition rates in naturally harsh (low pH caused by black-shale dominated geology) vs. circumneutral streams. We used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 65 publications
3
30
0
2
Order By: Relevance
“…A number of studies have shown that microbial communities are sensitive to changes in local environmental conditions (Duarte et al , Tolkkinen et al ). Our results are in agreement with these previous studies since leaf packs in near‐pristine streams and anthropogenically altered streams supported distinct fungal and bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that microbial communities are sensitive to changes in local environmental conditions (Duarte et al , Tolkkinen et al ). Our results are in agreement with these previous studies since leaf packs in near‐pristine streams and anthropogenically altered streams supported distinct fungal and bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing microbial biomass on leaf litter in nutrient enriched streams (Gulis & Suberkropp, ; Baldy et al ., ), successional shifts in fungal and bacterial groups during leaf‐litter decomposition (Das, Royer & Leff, ; Duarte et al ., ) and shifts in fungal and bacterial community composition in response to metal and other chemical contamination (Sridhar et al ., ; Duarte et al ., ; Solé et al ., ). Capitalising on advancements in DNA sequencing technologies, recent research has also aimed at better characterising the community composition of these leaf‐litter microbial communities in streams across different spatial scales and in the presence of anthropogenic disturbance (Tolkkinen et al ., , ; Heino et al ., ; Duarte et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…, Tolkkinen et al. ). Coarse containers were constructed from rubber‐coated wire (2.5‐cm mesh), and leaves in open packs were sewn together with 6‐lb monofilament line (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2a). A 500-lm mesh is a good size to exclude detritivores yet prevent hypoxia (Flores et al 2013, Tolkkinen et al 2015. Coarse containers were constructed from rubber-coated wire (2.5-cm mesh), and leaves in open packs were sewn together with 6lb monofilament line ( Fig.…”
Section: Feeding Experiments (Hypothesis 2)mentioning
confidence: 99%